FAKTOR-FAKTOR YANG MEMPENGARUHI KESEMPATAN KERJA SEKTOR INDUSTRI DAN JASA DI PROVINSI LAMPUNG - SITUMORANG, SURYATI (Lampung University)
The objective ofÂ research is to know : (1) performance of economicâs structure of Lampung Province related to occupationâs structure, Â (2) the factors which influence occupation on industry and services sector, and (3) response of industry and services sector to changing the factors which influential. The research employs time series data and analysed using econometric model with ordinary least squares (OLS).Â The result of Â research shows that : (1) the pattern of economicâs structure and occupationâs structure of Lampung Province is in the same direction, Agriculture â Industry â Services.Â (2) Generally, all of explanatory variables can explains the performance of occupation on industry and services sector model. (3) Occupation on industry sector influenced by Â GDRP (Gross Domestic Regional Product) and the amount of industryâs enterprises.Â Occupation on services sector influenced by industry occupation, agriculture occupation, and lag services occupation . Â (4) Occupation on industry sector does not responsive to changing all of explanatory variables. Occupation on services sector responsive to changing agriculture occupation.